Advancements in the impact of human microbiota and probiotics on leukemia - Zhang, Yi; Zhao, Xiaotong; Zhang, Jingxian; Zhang, Yaodong; Wei, Yongjun (Frontiers in Microbiology, 2024)
The human gut microbiota is a complex ecosystem that plays a crucial role in promoting the interaction between the body and its environment. It has been increasingly recognized that the gut microbiota has diverse physiological functions. Recent studies have shown a close association between the gut microbiota and the development of certain tumors, including leukemia. Leukemia is a malignant clonal disease characterized by the uncontrolled growth of one or more types of blood cells, which is the most common cancer in children. The imbalance of gut microbiota is linked to the pathological mechanisms of leukemia. Probiotics, which are beneficial microorganisms that help maintain the balance of the host microbiome, can play a role in regulating gut microbiota. Probiotics have the potential to assist in the treatment of leukemia and improve the clinical prognosis of leukemia patients. This article study reviews the relationship between gut microbiota, probiotics, and the progression of leukemia based on current research. In addition, utilizing zebrafish leukemia models in future studies might reveal the specific mechanisms of their interactions, thereby providing new insights into the clinical treatment of leukemia. In conclusion, further investigation is still needed to fully understand the accurate role of microbes in leukemia.